2021
DOI: 10.1007/s12026-021-09220-5
|View full text |Cite
|
Sign up to set email alerts
|

Neurological symptoms and axonal damage in COVID-19 survivors: are there sequelae?

Abstract: The persistence of neurological symptoms after SARS-CoV-2 infection, as well as the presence of late axonal damage, is still unknown. We performed extensive systemic and neurological follow-up evaluations in 107 out of 193 consecutive patients admitted to the COVID-19 medical unit, University Hospital of Verona, Italy between March and June 2020. We analysed serum neurofilament light chain (NfL) levels in all cases including a subgroup (n = 29) of patients with available onset samples. Comparisons between clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 13 publications
(18 reference statements)
2
16
0
Order By: Relevance
“… 19 , 29 , 34 Our findings are in line with studies that identified a correlation between NfL and/or GFAP with severity of reported neurologic symptoms during the acute phase, but found no association between the biomarker levels and persistence of neurologic symptoms after 6 months. 27 , 28 Further work exploring the dynamics of these markers in cohorts with measurements performed during the period of acute illness, as well as efforts to identify downstream markers which may persist and be identified during later recovery, will be informative.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 19 , 29 , 34 Our findings are in line with studies that identified a correlation between NfL and/or GFAP with severity of reported neurologic symptoms during the acute phase, but found no association between the biomarker levels and persistence of neurologic symptoms after 6 months. 27 , 28 Further work exploring the dynamics of these markers in cohorts with measurements performed during the period of acute illness, as well as efforts to identify downstream markers which may persist and be identified during later recovery, will be informative.…”
Section: Discussionmentioning
confidence: 99%
“… 26 However, there are limited data on the relationship between biomarkers of immune activation, neurologic injury, and neurologic symptoms during the postacute period. 17 , 27 - 29 …”
mentioning
confidence: 99%
“…Our findings are in line with studies that identified a correlation between NfL and/or GFAP with neurologic symptoms during the acute phase, but found no association between the biomarker levels and persistence of neurologic symptoms after six months. 39,40 Further work exploring the dynamics of these markers in cohorts with measurements performed during the period of acute illness, as well as efforts to identify downstream markers which may persist during later recovery, will be informative.…”
Section: Discussionmentioning
confidence: 99%
“…14 However, there are limited data on the relationship between biomarkers of inflammation, neurologic injury, and neurologic symptoms during the post-acute period. 25,39,40…”
Section: Introductionmentioning
confidence: 99%
“…Elevated CSF NFL levels have been observed in the majority of Covid-19 patients with neurological symptoms [ 14 ]; however, a study reported increased CSF NFL concentrations in Covid-19 patients with CNS syndromes, but not in those with peripheral nervous system (PNS) involvement, whereas sNFL levels were similarly augmented in all hospitalized Covid-19 patients, suggesting—together with the lack of correlation between CSF and serum NFL levels—that increases of NFL in the blood are partly determined by peripheral mechanisms [ 15 ]. Notably, blood NFL levels have been reported to normalize within 6 months after acute Covid-19 in a large majority of patients [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%